The Influence Of Transparency, Accountability, Community Participation On Village Fund Management In Realizing Good Governance In Mountain Villages In Tigabinanga District" Karo District - Mitha Christina Ginting; Arthur Simanjuntak; Septony B Siahaan; Duma Megaria Elisabeth; Juni Elisa Sari Ginting (Jurnal Ilmiah Accusi, 2024)
This research aims to analyze the influence of transparency, accountability, and community participation on the management of village funds in realizing good governance in villages in Tigabinanga District, Karo Regency. The sample size for this research was 30 village officials divided into four villages, namely Gunung, Kem - Kem, Kuta Raya, and Kuta Buara. The data analysis method uses multiple linear regression. The research results show that partial transparency has no significant effect on village fund management, while accountability and community participation have a positive and significant effect on village fund management. The results simultaneously show that transparency, accountability, and community participation have a significant effect on village fund management